A Review: Development of an IoT-Based Smart Home Monitoring System for the Comfort of People with Disabilities - Rara Anjela; Kisna Pertiwi; Sabar Sabar (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2024)
The advancement of the Internet of Things (IoT) has revolutionized smart home technology, providing enhanced comfort, security, and accessibility, particularly for people with disabilities. This review explores the development of IoT-based smart home monitoring systems designed to improve the quality of life for individuals with mobility, sensory, or cognitive impairments. By integrating IoT sensors, automation, and artificial intelligence (AI), smart home systems can provide real-time monitoring, adaptive control of household appliances, and emergency response mechanisms. The study highlights key technologies such as voice-controlled assistants, smart sensors, and remote accessibility features, which enable seamless interaction with home environments. Additionally, challenges related to data privacy, security risks, and affordability are discussed, along with potential solutions. The findings suggest that IoT-enabled smart home systems significantly enhance the independence and well-being of individuals with disabilities, emphasizing the need for continued innovation and policy support in this field. Keywords— Disability, Smart Home, Google Assistant, IoT.